2017
DOI: 10.1007/s11235-017-0327-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of end-to-end SNR estimators for AF relaying

Abstract: Many existing signal-to-noise ratio (SNR) estimators were designed and evaluated for conventional onehop communications systems. However, for a relaying system, it is the end-to-end SNR that determines the system performance. In this paper, we will fill this gap by evaluating the performances of the existing SNR estimators in a dual-hop relaying system used for each hop. The probability density functions of the SNR estimators are first derived, whose parameters are fitted as functions of the sample size and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In [17], estimators for individual channel coefficients were studied, and moment-based (MB) estimators were developed in [18] for individual channel power. In [19], the performances of different channel estimators in AF relaying with energy harvesting were compared. These estimators were developed for AF relaying without RF EH, where the pilots for channel estimation are sent from relay to destination using the relay's own power, in addition to the data transmission power.…”
Section: Introductionmentioning
confidence: 99%
“…In [17], estimators for individual channel coefficients were studied, and moment-based (MB) estimators were developed in [18] for individual channel power. In [19], the performances of different channel estimators in AF relaying with energy harvesting were compared. These estimators were developed for AF relaying without RF EH, where the pilots for channel estimation are sent from relay to destination using the relay's own power, in addition to the data transmission power.…”
Section: Introductionmentioning
confidence: 99%
“…Each relay i sends feedback to the source using the SNR value between the source and relay i as the input data to identify the best relay. The SNR of each relay was calculated as follows [25]:…”
Section: A Inter-clustering Model Imentioning
confidence: 99%
“…More specifically, the studies in [8], [9], [11] demonstrated that the employment of adaptive modulation in opportunistic relaying enhanced the spectral efficiency in cooperative relaying networks, by selecting the best relay node which provided the "best" end-to-end path between source and destination. Whilst, the authors in [10] studied the performance comparison of different channel estimators in AAF relaying. However, these studies considered SNR estimation in the frequency domain [8], [10], [11].…”
Section: A Related Workmentioning
confidence: 99%